Financial ratios and firm’s value: Evidence from Malaysia - Baba, Bello Usman; Abdul Manaf, Kamarul Bahrain (American Scientific Publishers, 2016)
This study empirically examines the effect of financial ratios on firm’s value.Specifically, it examines the effect of return on equity, return on assets and operating profit margin ratios on firm’s value. Market-to-book ratio is used as the measure for firm’s value. The study utilizes a sample of top 100 leading firms in Malaysia (Index Companies) for the period of 2008–2012. Using panel data regression analysis, the study reveals that profitability ratios have a significant effect on firm’s value.On the basis of the findings, the study concludes that there is increasing need for a more credible and comprehensive disclosure of financial ratios in the annual reports of firms.On this ground, the study recommends that Malaysian regulatory authorities implement a policy or a guideline that will encourage a uniform and comprehensive disclosure of financial ratios by firms. This in turn will avail investors and other users of financial information a better means of evaluating and making a qualitative judgment on firms’ financial performance.